CD4+ T Follicular Helper Cells in Human Tonsils and Blood Are Clonally Convergent but Divergent from Non-Tfh CD4+ Cells - Brenna, Elena; Davydov, Alexey N; Ladell, Kristin; McLaren, James E; Bonaiuti, Paolo; Metsger, Maria; Ramsden, James D; Gilbert, Sarah C; Lambe, Teresa; Price, David A; Campion, Suzanne L; Chudakov, Dmitriy M; et al. (Cell reports, 2020)
T follicular helper (Tfh) cells are fundamental for B cell selection and antibody maturation in germinal centers. Circulating Tfh (cTfh) cells constitute a minor proportion of the CD4+ T cells in peripheral blood, but their clonotypic relationship to Tfh populations resident in lymph nodes and the extent to which they differ from non-Tfh CD4+ cells have been unclear. Using donor-matched blood and tonsil samples, we investigate T cell receptor (TCR) sharing between tonsillar Tfh cells and peripheral Tfh and non-Tfh cell populations. TCR transcript sequencing reveals considerable clonal overlap between peripheral and tonsillar Tfh cell subsets as well as a clear distinction between Tfh and non-Tfh cells. Furthermore, influenza-specific cTfh cell clones derived from blood can be found in the repertoire of tonsillar Tfh cells. Therefore, human blood samples can be used to gain insight into the specificity of Tfh responses occurring in lymphoid tissues, provided that cTfh subsets are studied.
Keywords: Young Adult; Clone Cells; T follicular helper cells; blood; receptory CXCR3; krční mandle; mladý dospělý; folikulární pomocné T-buňky; Adolescent; Computer Simulation; Hemagglutinin Glycoproteins, Influenza Virus; Lymphocyte Subsets; velikost buňky; Adult; Tissue Donors; dospělí; dárci tkání; TCR repertoire; mladiství; buněčné klony; CD4-Positive T-Lymphocytes; lidé; Receptors, CXCR3; Humans; hemaglutininové glykoproteiny viru chřipky; T Follicular Helper Cells; influenza; počítačová simulace; tonsil; Palatine Tonsil; lidé středního věku; podskupiny lymfocytů; Cell Size; CD4-pozitivní T-lymfocyty; Middle Aged